1985
DOI: 10.1111/j.1600-0676.1985.tb00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune mechanisms for hepatic fibrogenesis. T‐lymphocyte‐mediated stimulation of fibroblast collagen production in chronic active hepatitis

Abstract: ABSTRACT— Lymphocytes can produce soluble factors capable of enhancing fibroblast proliferation and collagen synthesis. T‐lymphocytes, adherent cells and undifferentiated peripheral blood mononuclear cells from patients with HBsAg‐positive chronic active hepatitis and from HBsAg healthy carriers were triggered with purified HBsAg and tested for their ability to enhance collagen production by human dermal fibroblast cultures. Purified HBsAg did not induce any proliferative response in the mononuclear cell cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 12 publications
0
13
1
Order By: Relevance
“…Though innate immune activation and TH1 cytokines have been found to escalate NASH progression several research reports also stress upon the involvement of hepatic T cells in the progression of NASH (1114). Liver mononuclear cells, especially the CD4+ve, CD8+ve, NK and NKT cells are abundant in the liver and certain cells like NKT cells are deemed to be part of innate immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Though innate immune activation and TH1 cytokines have been found to escalate NASH progression several research reports also stress upon the involvement of hepatic T cells in the progression of NASH (1114). Liver mononuclear cells, especially the CD4+ve, CD8+ve, NK and NKT cells are abundant in the liver and certain cells like NKT cells are deemed to be part of innate immune system.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that co‐culturing T cells with fibroblasts leads to an upregulation of a number of different pro‐inflammatory cytokines by fibroblasts, either by direct contact between the two cells [Bombara et al, ; Rezzonico et al, ; Chizzolini et al, ] or through release of soluble factors in the conditioned media by the T cells [Mikko et al, ; Loubaki et al, ]. Furthermore, a few studies have shown that co‐culture of leukocytes with fibroblasts leads to changes in the expression of genes for ECM components such as collagen and the enzymes that degrade these components such as collagenase [Casini et al, ; Mikko et al, ]. However, there have been no studies that have evaluated whether other ECM components are involved and if these ECM changes further alter the pattern of leukocyte adhesion to the ECM.…”
mentioning
confidence: 99%
“…Herein, we provide further evidence that VAP‐1 is a good target to ameliorate the autoimmune‐induced hepatic injury by selectively regulating recruitment of CD4 Th2 but not Th1 lymphocytes. We analyzed the effect of anti‐VAP‐1 therapy for lymphocyte recruitment to the liver using a well‐established Con A‐induced hepatitis model . Con A treatment caused acute liver injury as assessed by increased serum transaminase level as early as 4 hours (data not shown) after intravenous administration and continued until 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Although T‐cell‐mediated immune responses play an important role in the development and progression of autoimmune, viral, and alcoholic hepatitis, the underlying mechanisms are still unclear. Concanavalin A (Con A)‐induced hepatic injury is a well‐established murine experimental model of T‐cell‐mediated autoimmune or viral hepatitis that shares several pathological features with the disease in humans . The Con A model also serves to elucidate mechanisms of infiltration and activation of T cells in the liver that are critical for the development of human autoimmune and viral hepatitis .…”
mentioning
confidence: 99%
See 1 more Smart Citation